The Influence of Light on Olive (Olea europaea L.) Fruit Development Is Cultivar Dependent - Reale, Lara; Nasini, Luigi; Cerri, Martina; Regni, Luca; Ferranti, Francesco; Proietti, Primo (Frontiers in Plant Science, 2019)
In olive, the response to environmental conditions, such as light availability, is under genetic control and requires a combination of biochemical and physiological events. We investigated the effect of irradiance in fruit development in two Italian cultivars, Leccino and Frantoio. Morphological and cyto-histological analyses, as well as water and oil content determination, were carried out in fruits exposed to a different light regime (named as light and shaded fruits). Results demonstrated that the influence of light availability on fruit development depends on the cultivar. In Leccino, the fresh and the dry weight, the percentage of dry matter, the kernel and fruit diameter, the mesocarp thickness and the mesocarp cell size were higher in the light exposed fruits than in the ones grown in the shade. In Frantoio, differences between light and shade fruits were observed only at 140 DAF (Days After Flowering) and only in the kernel and fruit diameter and in the dry and fresh weight, which were higher in the light exposed fruits. Leccino, therefore, showed a greater sensitivity to the light availability. This may be related to the observed delay in the endocarp lignification as compared to the Frantoio cultivar. In each cultivar, moreover, shade and light fruits did not show differences in the timing of cell differentiation. Finally, the investigation of oil storage carried out in cyto-histological studies demonstrated that differences in oil content between fruit subjected to different light regimes correlated with the number of oil containing cells, rather than the oil content per cell. A different behaviour was observed in the two cultivars: in Leccino, the mesocarp cell size was almost twice of Frantoio, while oil drops were only 30% larger; therefore, the percentage of cell volume occupied by the oil drops was lower in Leccino than in Frantoio. The chemical analysis confirmed this observation.